Pengaruh Rights Issue terhadap Imbal Hasil Saham dan Volume Perdagangan - CATRANTI, ASKI (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The study is to find out the major type of institutional investors who own the biggest fund in the capital market and to study their behaviors which can affect the market. There are three types of investors: intuitive investors, emotional investors, and rational investors. To analyze the main factor of decision making, the researcher used Analytical Hierarchy Process (AHP) and spread questionnaires to several Indonesian fund managers. The result shows that most institutional investors are rational (55%), 45% are emotional and none of them are intuitive. The main factor influencing them to make an investment decision is the country’s economic conditions (25.12%), along with accounting information (liquidity, rentability, solvability, and quality of financial reports).